Barron' s how to prepare for............... - Sharp, Pamela (Lahore: Jahangir Book Depo, 2007)
When Donald Ray Lindengraf angrily shoves his little brother Jimmy in the bathtub, he has no idea that he will send Jimmy down on a stream of angry water to the river under the bathtub and into the arms of the sea goblins below. With the help of Dashell, a proud and pompous penguin, and Trumbell, a kind and trusty sea elephant, Donald must chase his brother to goblin caves and rescue him there, then return speedily home. If they don$1 (Bt get home before their mother lets out the bathwater, they will lose their way back to the human world. This adventure story for children touches on the subjects of controlling one$1 (Bs temper, taking responsibility for one$1 (Bs actions, loyalty to one$1 (Bs friends, and seeing oneself in a new, more positive light. As Trumbell says, (3z(BA chap makes a hero of himself, don$1 (Bt you know?(3y (BA lesson learned by characters in the story, and a message a young reader may ts
Kindle eBook.